Analisis Tingkat Literasi Keuangan Siswa SMK Batik di Kota Surakarta - Ayu, Dyah; Sari, Dhany Efita (Universitas Hamzanwadi, 2025)
This study aims to analyze the level of financial literacy of SMK Batik Surakarta students, what programs are implemented to improve students financial literacy at SMK Batik Surakarta, and identify the results of a comparison of the level of financial literacy of SMK Batik Surakarta students. The research method used is qualitative and based on case studies. Data were collected throygh intervies, observation, and documentation with students and teachers at SMK Batik 1&2 Surakarta. The data analysis technique for this study used interactive analysis by Miles, Huberman, and Salda which were then analyzed using the NVivo 15 application. The results showed that the level of financial literacy of students in both school was still low, wih significant differences in facilities and programs supporting financial literacy. SMK Batik 1 has a Bank Mini Syariah, while SMK Batik 2 does not have similar facilities. Strengthening facilities, structured programs, and evaluations are needed to improve students’ financial literacy as a whole